2019
DOI: 10.3390/su11226305
|View full text |Cite
|
Sign up to set email alerts
|

A Study and Factor Identification of Municipal Solid Waste Management in Mexico City

Abstract: Mexico City generates 12 thousand tons of Municipal Solid Waste (MSW) per day, which places it as one of the cities that produces the most MSW in the world. However, the treatments used in the city are not enough for recycling materials and organics valorization of at least 45% of the MSW, which is the minimum for a medium-high-income city. To put in a global context the deficiency in Municipal Solid Waste Management (MSWM) in Mexico City and evaluate the policies that have been implemented thus far, Wasteawar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…The squares in dotted lines in Figure 1 indicate the activities carried out by the inhabitants. Since the separation of all MSWs has not yet been achieved, a part of them is collected mixed; it is shown in the figure that there are two different types of storage, mixed and buried [10]. In Mexico City, there are 1888 colonies or towns distributed in the 16 municipalities that make up the city, and each of them is served by a collection route.…”
Section: Solid Waste Management In Mexico Citymentioning
confidence: 99%
See 1 more Smart Citation
“…The squares in dotted lines in Figure 1 indicate the activities carried out by the inhabitants. Since the separation of all MSWs has not yet been achieved, a part of them is collected mixed; it is shown in the figure that there are two different types of storage, mixed and buried [10]. In Mexico City, there are 1888 colonies or towns distributed in the 16 municipalities that make up the city, and each of them is served by a collection route.…”
Section: Solid Waste Management In Mexico Citymentioning
confidence: 99%
“…The management of MSW is a challenge for the mayors in charge of the collection due to traffic density. According to current environmental regulations, the city government is in charge of the treatment and final disposal of the MSW for the amount generated and the lack of adequate areas within its territory [10]. Three different groups carry out the integral management of the MSW in Mexico City: the public cleaning service that performs the sweeping, collection, transport, and final disposal and treatment; the informal workers that carry out the manual separation of the MSW for recycling; and the private companies in charge of the industrial collection and recycling centers [9].…”
Section: Introductionmentioning
confidence: 99%
“…Managing solid waste presents significant challenges for local governments in developing countries. Despite increasing volumes of solid waste, the majority of these countries lack adequate labor, money, equipment, knowledge, public services and other resources to manage waste in an environmentally safe manner [1]. A study of global MSWM found that service coverage was poor in low-income nations, and that in middle income countries there was a significant volume of garbage in open-dump sites with little or no environmental protection [2].…”
Section: Introductionmentioning
confidence: 99%
“…Wasteaware indicators can be applied in any city to assess MSWM performance. Galicia et al applied the indicator to obtain a desired profile for comprehensive MSWM in Mexico City which helped in addressing the weaknesses and strengths of its MSWM [1]. Azevedo et al [17] applied WABIs to case studies to do cross-case analysis to find drivers and governance strategies and for feasibility discussions and improvement possibilities.…”
Section: Introductionmentioning
confidence: 99%
“…Global population growth, economic development and urbanization have led to an increase in resource consumption and, consequently, in waste production, the management of such waste being a universally important issue [1]. As an example, 2010 million tons of municipal solid waste were generated worldwide in 2016, and at least 33% was inadequately managed [2]. In 2050, waste generation is expected to increase to 3400 million tons if no change occurs [3].…”
Section: Introductionmentioning
confidence: 99%